A cross-sectional study of the association of postnatal growth and psychosocial development of the infants in an urban slum of Delhi - Meenakshi; Pradhan S; Prasuna J (Wolters Kluwer Medknow Publications, 2007)
Background: Rapid growth of urban slums due to alarmingly increasing urbanization is adversely affecting the growth and development of infants residing in such deprived areas. Objectives: To study the association of postnatal growth and psychosocial development of urban slum infants. Methods: 202 infants and their mothers were included in a cross-sectional study conducted in Raja bazaar in 2002. Growth was assessed using anthropometric measurements: weight & length for age and development by psychosocial developmental scale developed by ICMR. Results: Development was delayed in significantly higher percentage of underweight (W/A<-2 S.D) than normal infants (p value< 0.05): gross motor (15.3%& 4.5%), Vision &fine motor (21.1%, 4.6%) and social skills (27.6%, 12.1%). Development of gross motor milestones was also delayed in significantly high percentage of stunted infants with L/A<-2S.D (22.2%) compared to normal L/A (5.6%, p value=0.003). Difference in the percentages of infants was significantly very high (p value0.000) for vision & fine motor (27.5% & 6.9 %), hearing, language & concept development (22.5% & 4.2%) and social skills (42.5% & 11.9%). Conclusions: Interventions to improve the postnatal growth will be helpful in facilitating the psychosocial development of infants living in urban slums.